(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The structural components related to the content of the educational process, as a social phenomenon, are manifested as a methodological aspect of teaching theory in linguodidactics, which is connected to the nature of language and communication. Linguodidactics, when studying issues related to analyzing, managing, and modeling the processes of language acquisition, refers to the mechanisms of learning both the native and foreign languages, describing and explaining the processes that form the internal structure.